Influence of running pace upon performance: Effects upon oxygen intake, blood lactate, and rating of perceived exertion - Ariyoshi, M.; Tanaka, H.; Kanamori, K.; Obara, S.; Yoshitake, H.; Yamaji, K.; Shepard, R. J. (Canadian Journal of Applied Sport Sciences, 1979)
Several general performance protocols for running a middle-distance event were compared. A treadmill (1,400 m; 4 min) run was evaluated at a fast/slow, slow/fast, and steady pace speed distribution. The fast/slow protocol resulted in a rapid and sustained increase in oxygen uptake, less lactate accumulation, and a lower rating of perceived exertion during the final 2 min of the 4 min run. Implication: Fast/slow pacing is superior to the other protocols. This is possibly due to the match of effort demanded with progressively waning physiological power.